2022
DOI: 10.7326/m22-0924
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Baseline Plasma SARS-CoV-2 Nucleocapsid Antigen Level and Outcomes in Patients Hospitalized With COVID-19

Abstract: In a large cross-sectional study done in 114 centers in 10 countries, the authors assessed whether there was an association of an elevated SARS-CoV-2 plasma antigen level at presentation with a variety of patient characteristics, clinical outcomes, and viral factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 36 publications
3
20
0
Order By: Relevance
“…Our study also demonstrates a strong association of SARS-CoV-2 nucleocapsid viral antigen with development of severe disease in COVID-19, consistent with several prior studies of hospitalized patients ( 14 , 19 , 20 , 40 ). Recent data from a large multicenter clinical trial consortium demonstrated that in patients hospitalized with COVID-19, higher SARS-CoV-2 nucleocapsid viral antigen measured within the first 72 hours was associated with worse clinical outcomes at 7 days ( 19 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study also demonstrates a strong association of SARS-CoV-2 nucleocapsid viral antigen with development of severe disease in COVID-19, consistent with several prior studies of hospitalized patients ( 14 , 19 , 20 , 40 ). Recent data from a large multicenter clinical trial consortium demonstrated that in patients hospitalized with COVID-19, higher SARS-CoV-2 nucleocapsid viral antigen measured within the first 72 hours was associated with worse clinical outcomes at 7 days ( 19 ).…”
Section: Discussionsupporting
confidence: 91%
“…The soluble receptor for advanced glycation end-products (RAGE) and SARS-CoV-2 nucleocapsid viral antigen are two biomarkers recently shown to have prognostic value in hospitalized patients with COVID-19 ( 12 14 ). However, few studies to date have examined these biomarkers in patients presenting to the emergency department.…”
Section: Introductionmentioning
confidence: 99%
“…During the first week of the SARS-CoV-2 infection, detection of N in plasma has a sensitivity of > 90% for the infection with concentration positively correlated to disease severity 8 . Quantification of viremia by N in plasma can therefore be used for risk stratification and/or as a prospective marker for poor outcome in COVID-19 patients 4 , 9 12 . However, quantitative assays should have a sensitivity and specificity needed for answering the clinical question raised e.g.…”
Section: Introductionmentioning
confidence: 99%
“…First of all, this antigen can be directly detected in biological fluids for the purpose of diagnosis in the early stages of infection. The specificity and relatively high sensitivity of this direct analysis has been shown in fluorescence immunochromatographic (FIC) assays [ 15 ] and ELISA tests [ 16 , 17 ]. Moreover, strong positive correlation was observed between elevated plasma N-antigens and odds of pulmonary damage severity, resulting in worsened clinical outcomes [ 17 , 18 ]; therefore, N-level measurement upon hospital admission may improve risk stratification through identification of patients with implicit odd of severe diseases [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The specificity and relatively high sensitivity of this direct analysis has been shown in fluorescence immunochromatographic (FIC) assays [ 15 ] and ELISA tests [ 16 , 17 ]. Moreover, strong positive correlation was observed between elevated plasma N-antigens and odds of pulmonary damage severity, resulting in worsened clinical outcomes [ 17 , 18 ]; therefore, N-level measurement upon hospital admission may improve risk stratification through identification of patients with implicit odd of severe diseases [ 18 ]. An N-antigen-based assay may be performed in a simple self-test format, although its sensitivity and diagnostic accuracy would be lower compared to those of an RT-PCR assay [ 19 ].…”
Section: Introductionmentioning
confidence: 99%